2018
DOI: 10.1371/journal.pone.0207387
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation biomarkers and prediction of venous thromboembolism and survival in small cell lung cancer: A sub-study of RASTEN - A randomized trial with low molecular weight heparin

Abstract: Coagulation activation and venous thromboembolism (VTE) are hallmarks of cancer; however, there is an unmet need of improved biomarkers for individualized anticoagulant treatment. The present sub-study of the RASTEN trial was designed to explore the role of coagulation biomarkers in predicting VTE risk and outcome in a homogenous cancer patient population. RASTEN is a multicenter, randomized phase-3 trial investigating the survival effect of low molecular weight heparin enoxaparin when added to standard treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
3
33
1
Order By: Relevance
“…13 Importantly, increased levels of EV TF activity were associated with venous thromboembolism in patients with pancreatic cancer but not in other types of cancer including brain, colorectal, ovarian, and lung cancer. 13,16,22,23 Interestingly, patients with cirrhosis and acute liver injury have 17-fold and 38-fold increased levels of EV TF activity compared with healthy controls, respectively. 13 Increased levels of EV TF were detected in patients with endotoxemia (nine-fold) and urinary tract infection (six-fold).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Importantly, increased levels of EV TF activity were associated with venous thromboembolism in patients with pancreatic cancer but not in other types of cancer including brain, colorectal, ovarian, and lung cancer. 13,16,22,23 Interestingly, patients with cirrhosis and acute liver injury have 17-fold and 38-fold increased levels of EV TF activity compared with healthy controls, respectively. 13 Increased levels of EV TF were detected in patients with endotoxemia (nine-fold) and urinary tract infection (six-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer has the highest EV TF activity (16‐ to 26‐fold higher than healthy controls) among different types of cancer . Importantly, increased levels of EV TF activity were associated with venous thromboembolism in patients with pancreatic cancer but not in other types of cancer including brain, colorectal, ovarian, and lung cancer . Interestingly, patients with cirrhosis and acute liver injury have 17‐fold and 38‐fold increased levels of EV TF activity compared with healthy controls, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…124 Moreover, a substudy of the RASTEN trial, including 242 small cell lung cancer patients, failed to show a correlation between EV TF activity and VTE. 125 In 648 advanced cancer patients (esophagus, lung, colorectal, pancreas, breast, gastric, ovarian, prostate and bladder cancer), van Es et al recently showed that EV TF activity was associated with a twofold increased risk of VTE. In agreement with observations described earlier in this paragraph, this association was demonstrated to be much stronger in pancreatic cancer (4.1-fold increased risk) than in other tumor types (1.5-fold increased risk).…”
Section: Tf-positive Extracellular Vesiclesmentioning
confidence: 99%
“…As venous thrombosis and thromboembolism are risk factors for a dismal outcome, one study group focused on the additional use of low-molecular-weight heparin anticoagulants in SCLC treatment. Yet, the overall survival improved by the concomitant use of enoxaparin [60] nor was a biomarker established for predicting the risk of venous thrombosis and thromboembolism in SCLC patients [61]. Other than that, redox status and lipid metabolism were shown to be altered in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%